1995
DOI: 10.1111/j.1399-3054.1995.tb05312.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of dormancy and sink strength in sprouting of onions (Allium cepa) during storage

Abstract: In onion (Allium cepa L.) postponement of sprouting is necessary to achieve long term storage. We studied the factors determining sprouting during dry storage at 16°C. The period to visible sprouting depends on the length of the dormancy period, if present, and on the growth rate of the sprout. In the three cultivars tested, sprouts were initiated within 2 weeks after harvest indicating the absence of a real dormancy period. Sprout length increased linearly during storage. The mitotic activity of the apex decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…In the dormant phase, supposedly started Acta Agriculturae Scandinavica, Section B -Soil & Plant Science 3 near harvest (Miedema 1994;Yasin & Bufler 2007), many physiological processes are slowed down, although not ceased (Pak et al 1995;Yasin & Bufler 2007;Brewster 2008). After the dormancy breaking, onion bulbs enter the regrowth phase that is accompanied by gradually increasing metabolic activity.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In the dormant phase, supposedly started Acta Agriculturae Scandinavica, Section B -Soil & Plant Science 3 near harvest (Miedema 1994;Yasin & Bufler 2007), many physiological processes are slowed down, although not ceased (Pak et al 1995;Yasin & Bufler 2007;Brewster 2008). After the dormancy breaking, onion bulbs enter the regrowth phase that is accompanied by gradually increasing metabolic activity.…”
Section: Resultsmentioning
confidence: 98%
“…A similar conclusion was drawn by Kaack et al (2004), who observed a variation in DM from 9.2 to 14.4 g 100 −1 g as a function of cultivar, whereas a six month storage at 5°C had no measurable effect on this quantity. On the contrary, Pak et al (1995) have observed an approximately 9% decrease in DM of onion bulbs cv. Hysam.…”
Section: Weight Loss and Dm Contentmentioning
confidence: 83%
See 3 more Smart Citations